A case report of severe systemic infection with neurological HFMD symptoms followed by an accidental puncture of thumb during HFMD sample collection. (2022) - Zare, Maryam; Jamalidoust, Marzieh; Pouladfar, Gholam R.; Amanati, Ali; Shafaati, Maryam; Namayandeh, Mandana; Ziyaeyan, Mazyar
Abstract: A 34-year-old female clinical virology assistant was punctured with a contaminated lancet used for sampling from a suspected Hand, Foot, and Mouth disease (HFMD) patient. Five days after a puncture, the disease symptoms manifested, including high fever, ague, and stiff neck. Skin rashes suddenly appeared after day 6. Stiff neck and fever were relieved two days after the rash appeared, and rashes disappeared gradually by the next five days. Samples for molecular detection and virus cultivation were taken from the patient. Real-time PCR found the enteroviral RNA in the throat swab and skin rashes. The specific CPE of Enteroviruses appeared on the Vero cell line after three days of incubation. In this case transmission occurs through needle injury and results in the systemic disease, so unusual and unexpected viral transmission should be considered when dealing with samples. Highlights: Hand, foot, and mouth disease is a common disease in kids that causes lesions inside or around their lips and a rash or vesicles on their fingers, feet, legs. The transmission route HFMD through needle injury resulting in systemic disease is not a usual incidence and should be considered when dealing with samples. Oral lesions may occur without cutaneous rashes. In the case we reported, oral lesions were absent in this patient.